2013
DOI: 10.1088/1367-2630/15/3/035011
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model for the subgrid timescale experienced by heavy particles in large eddy simulation of isotropic turbulence with a stochastic differential equation

Abstract: The effects of subgrid scale (SGS) motions on the dispersion of heavy particles raise a challenge to the large-eddy method of simulation (LES). As a necessary first step, we propose the use of a stochastic differential equation (SDE) to represent the SGS contributions to the relative dispersions of heavy particles in LES of isotropic turbulence. The main difficulty is in closing the SGS-SDE model whilst accounting for the effects of particle inertia, filter width and gravity. The physics of the interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 67 publications
(146 reference statements)
0
11
0
1
Order By: Relevance
“…Particles follow the motion of the large eddies but slip predominantly on the small ones: This dynamics is characterized by particle-to-fluid relative velocities much smaller than u l and hence by small particle Reynolds numbers. In the following, we will focus on the models that have been developed in this regime (see [31,55,62,117] among others). In the opposite limit (St SG S >> 1), particles become SGS-inertial with respect to subgrid eddies [125], and (in principle) no particle SGS model is necessary: The dominant eddies controlling the relative velocity are resolved in LES, and the corresponding velocity u is enough to solve Eq.…”
Section: Governing Equations and Relevant Modelling Parametersmentioning
confidence: 99%
“…Particles follow the motion of the large eddies but slip predominantly on the small ones: This dynamics is characterized by particle-to-fluid relative velocities much smaller than u l and hence by small particle Reynolds numbers. In the following, we will focus on the models that have been developed in this regime (see [31,55,62,117] among others). In the opposite limit (St SG S >> 1), particles become SGS-inertial with respect to subgrid eddies [125], and (in principle) no particle SGS model is necessary: The dominant eddies controlling the relative velocity are resolved in LES, and the corresponding velocity u is enough to solve Eq.…”
Section: Governing Equations and Relevant Modelling Parametersmentioning
confidence: 99%
“…New methods in numerical simulations. On the numerical aspects, new strategies of largeeddy-simulations (LES) are proposed, with novel sub-grid scale models based on a stochastic differential equation to account for particles inertia [1] and coupling hybrid Eulerian-Lagrangian approaches [2], improving the capacities of LES to handle pair separation and collisions for point-like particles. A long standing limitation of simulations of particles in turbulence was their insufficient capability to address the effects of finite particle sizes, as usual models for particle motion are based on the Maxey-Riley-Gatignol equation that was derived for particles with vanishingly small sizes [3,4] 3 .…”
Section: Methodological Advancesmentioning
confidence: 99%
“…The case of small, heavy particles, whose dynamics can be reasonably approximated using the linear Stokes equation (with the Stokes number as the only parameter characterizing particle inertia), has been extensively investigated numerically in recent decades using high resolution DNS in homogeneous isotropic conditions. The knowledge accumulated from this canonical situation offers a solid ground for the development of new numerical strategies in more realistic flow configurations using LES, as mentioned above [1,2], and for addressing more complex situations where collective effects can arise (see section 5).…”
Section: Single Particle Dynamics Of Inertial Particles and Finite-simentioning
confidence: 99%
“…Besides, in the simulation of heavy particles, it is also found that the choice of subgrid model is related to the computational accuracy of particles [30][31][32][33][34]. The aim of the research on resolved-scale scaling law is to provide a better tool for the subgrid modeling in LES.…”
Section: Applications Of Resolved-scale Scaling Law In Lesmentioning
confidence: 99%